Langerhans cell histiocytosis in an infant: a case report - Singhal, Nehal; Nagar, Rajendra; Nagori, Gautam (International Journal of Contemporary Pediatrics, 2022)
Langerhans cell histiocytosis is a rare non-malignant disease characterized by a clonal proliferation of pathological cells with the characteristics of Langerhans cells in single or multiple sites. A 7-month-old infant presented with continued fever and recurrent cough with progressive rash over the whole-body including palms and soles for over a month. On examination there was respiratory distress, generalized lymphadenopathy, hepatosplenomegaly and skin rash. The diagnostic workup for underlying causes showed ground glass opacity, pulmonary oedema and retroperitoneal lymphadenopathy on CT scans of thorax and abdomen respectively. The histopathology specimens of skin and lymph node biopsy further confirmed the suspicion of Langerhans cell histiocytosis. The patient was sent for treatment with vinblastine and prednisone to a higher centre. In this case report we highlighted the unusual presentations and prognosis of a child with Langerhans cell histiocytosis.